Knowledge, Attitude and Practice Among Covid-19 Health Care Workers A Quantitative Study on the Covid 19 Health Care Workers of Sindh Infectious Disease Hospital Karachi Pakistan - Rizwana Salik Nukrich, Haseeb U Rehman, Saba Afshan, Muhammad Azhar Ahmed, Khair Jan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: As per the World Health Organization (WHO), the coronavirus diagnosis 2019 (COVID-19) increase in the prevalence has turned into a pandemic, to date world has witnessed 5 waves of COVID- and it has now infected over 200 countries / regions, resulting in over 7.5 million infections and 4,19,568 fatalities worldwide Objective: To assess the knowledge, attitudes, and practices among COVID-19 Health care workers of COVID-19. Methodology: This was cross sectional studyand carried at Sindh Infectious Disease Hospital and Research Centre (SIDH & RC), a specialized COVID-19 hospital. Data will be collected through questionnaires and the respondents will be healthcare workers (doctors/medical practitioners and nurses) dealing with COVID 19 patients. Data was analysed by the SPSS version: 21. Result: In total, there are 111 participants; 56.8% of them are male COVID-19 health care workers Most of the Healthcare worker age range was 21-30 years. The received responses from 3 persons aged 51 and older, which represented 2.7% of the total population. The knowledge attitude and practices among the COVID-19 health care workers and all of them found that Awareness of COVID-19 among medical professionals is high. As people age, they get a more mature perspective on COVID19 infection, which in turn leads to more responsible behavior. Conclusion:89% of the healthcare professionals who were evaluated have the necessary understanding of COVID-19. On the basis of the findings of this research, future efforts to increase awareness and educate people can more effectively target specific knowledge and practice gaps.